INTERVENTION OF DEPRESSION MANAGEMENT AMONG ADOLESCENTS AS THE VICTIMS OF BULLYING: A LITERATURE REVIEW - Nadiya Sahara Annisa; Hanik Endang Nihayati (Indonesian Journal of Community Health Nursing, 2022)
Introduction: Bullying can cause various symptoms in psychological, physical and emotional. Bullying behavior can cause depression, anxiety and low self-esteem on victims of bullying. Interventions to overcome depression in adolescents victims of bullying consist of individual interventions and group interventions. This study aims to explain the interventions or program that can be done to overcome depression in adolescents victims of bullying. Method: Searching articles used Medical Subject Heading (MeSH) with keywords of Intervention OR Program AND Depression OR Depressive Symptoms AND Bullying OR Cyberbullying AND Adolescents OR Teenagers OR Young Adult OR Junevile. This research used academic databases including: Scopus, CINAHL, ScienceDirect with inclusion criteria include: adolescents aged 12-21 who are victims of bullying, articles published in 2011-2021 using experimental studies and in English and using The Joanna Briggs Institute (JBI) Critical Appraisal method. Results: A total of 10 articles were analyzed in this research. Findings articles were divided into two sections, namely individual interventions (n=2) and group interventions (n=8). Conclusions: This research showed that several interventions or programs that have been studied effectively can overcome depression or depressive symptoms in adolescents who have been victims of bullying. It is expected to educate adolescents on how to cope with depression or depressive symptoms of adolescents victims of bullying.   Keywords: Intervention, Depression, Bullying, Adolescents